Uptake and Release of Abscisic Acid by Isolated Photoautotrophic Mesophyll Cells, Depending on pH Gradients - Kaiser, Werner M. (1981)
Uptake and release of abscisic acid (AbA) by isolated mesophyll cells of Papaver somniferum is characterized by the following observations: (a) Uptake rate is a linear function of the external AbA concentration in the range from 10(−6) to 5 × 10(−5) molar, and decreases with increasing pH. At any pH, uptake rate is linearly related to the concentration of undissociated abscisic acid, calculated from the pK = 4.7 according to the Henderson-Hasselbalch equation. At low external pH (5.0), AbA accumulation in the cells is about 10-fold. (b) Uptake of AbA is completely inhibited by salts such as KNO(2) or sodium acetate, which decrease the pH gradient between medium and cells. KCN or m-chlorocarbonylcyanide phenylhydrazone inhibits AbA uptake only after longer incubation periods (20-40 minutes). (c) Uptake rate as well as equilibrium concentration is significantly higher in light than in darkness. (d) At low external pH, release of AbA from preloaded cells is strongly stimulated by KNO(2). It is concluded that AbA is distributed between leaf cells and free space according to pH gradients, with the undissociated abscisic acid being the main penetrating species. Uptake and release occur via diffusion, without participation of a carrier.